Peritoneal fluid as an index of peritoneal health in buffaloes with dystocia due touterine torsion - Brari, P S; Nanda, A S; Prabhakar, S; Sharma, D K (The Indian Journal of Animal Sciences, 2011)
Investigations were conducted on peritoneal fluid to assess the changes in peritoneal cavity of buffaloes suffering from uterine torsion. Peritoneal fluid was collected aceptically after correction of uterine torsion and delivery of fctlls (20) and after normal calving (n=5). The volume of peritoneal fluid drained through a single intra-peritoneal prick given around umbilicus was significantly more than normal in dystocia affected buffaloes (average 20 ml vs 5 ml). The normal peritoneal fluid was colourless and odourless whereas it was light to dark brown with no smell in torsion cases. Compared to normal, the peritoneal fluid of uterine torsion affected buffaloes had significantly higher neutrophil count (66.7±6.61 vs 14.0±2.7%), lower lymphocytic count (28.12±5.41 vs 78.00±3.57%) and a nonsignificantly decreased total leucocytic count. The concentration oftotal proteins (3.11 ±O.24 g/dl) and ofalbumen (2.97±0.23g/dl) in peritoneal fluid of buffaloes with uterine torsion was significantly higher as compared to corresponding values (1.97±0.31 and 1.87±0.31 g/dl) in the normally calved buffaloes. The concentration of immunoglobulins, however, was only marginally higher than normal in the uterine torsion cases. The peritoneal and uterine fluids from normally calved buffaloes were bacteriologically sterile, whereas both the fluids from dystocia buffaloes were infected. Same bacterial isolates were obtained from peritoneal as well as from the uterine fluids of each individual animal suggesting the contamination of peritoneal cavity by the uterine fluid. It was concluded that the buffaloes with uterine torsion were having severe peritonitis and that the contents of peritoneal cavity were infected bacteriologically.